1993
DOI: 10.1366/0003702934334804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Energy and Atmosphere on the Emission Characteristics of Laser-Induced Plasmas

Abstract: The effects of laser energy and atmosphere on the emission characteristics of laser-induced plasmas were studied with the use of a Q-switched Nd: YAG laser over a laser energy range of 20 to 95 mJ. Argon, helium, and air were used as surrounding atmospheres, and the pressures were changed from atmospheric pressure to 1 Torr. The experimental results showed that the maximum spectral intensity was obtained in argon at around 200 Torr at a high laser energy of 95 mJ, whereas the line-to-background ratio was maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…3 that LIBS signal increases monotonically with laser energy until the plasma density becomes too high for laser energy of 120 mJ. At still higher laser energy, the dense plasma formed by leading laser pulse starts absorbing energy from the later part of the laser pulse which leads to higher continuum emission [13,6] and lowers the analyte signal. Therefore, at higher energy, the decrease in LIBS signal may be due to shielding of laser light reaching to ablation surface.…”
Section: Methodsmentioning
confidence: 90%
“…3 that LIBS signal increases monotonically with laser energy until the plasma density becomes too high for laser energy of 120 mJ. At still higher laser energy, the dense plasma formed by leading laser pulse starts absorbing energy from the later part of the laser pulse which leads to higher continuum emission [13,6] and lowers the analyte signal. Therefore, at higher energy, the decrease in LIBS signal may be due to shielding of laser light reaching to ablation surface.…”
Section: Methodsmentioning
confidence: 90%
“…7,8 In order to find the optimum laser energy giving a high spectral line intensity, the emission intensity of the Pb I 405.78-nm line was measured by changing the laser pulse energy from 10 to 90 mJ. The result is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We studied the emission characteristics of the laser-induced plasma to improve the analytical performance, and showed the optimum conditions for quantitative analysis for non-conducting as well as conducting materials. [5][6][7][8][9][10][11][12][13] In our recent works, 14,15 we analyzed trace heavy metals of Pb, Cd, Hg and Cr in plastics by LIPS in argon at reduced pressure using time-resolved spectroscopy, and showed that these metal elements can be determined with detection limits of several tens ppm, and that the LIPS technique can be used for screening plastics for regulated elements.…”
Section: Introductionmentioning
confidence: 99%
“…At high laser energy, the plasma absorbs more laser energy and increases the plasma temperature, which leads to higher continuum emission. 28 The decrease in intensity of atomic lines may be due to shielding of laser light reaching to ablation surface or to loss in content of plasma energy due to generation of instability. Self-absorption may also contribute to the decrease in line emission intensity.…”
Section: Laser Energymentioning
confidence: 99%